Association of birth weight with abdominal obesity and weight disorders in children and adolescents: the weight disorder survey of the CASPIAN-IV Study - Hossein Ansari (Journal of Cardiovascular and Thoracic Research, 2017)
Introduction: This study aims to evaluate the association of birth weight (BW) with weight disorders in a national sample of Iranian pediatric population. Methods: This nationwide survey was conducted among 25000 student’s aged 6-18 year-old students, who were selected using multistage cluster random sampling from 30 provinces of Iran in 2011-2012. Anthropometric measures were measured under standard protocols by using calibrated instruments. Abdominal obesity was defined based on waist circumference (WC) ≥90th percentile value for age and sex. The WHO criterion was used to categorize BMI. Students’ BW was asked from parents using validate questionnaire and was categorized as low BW (LBW) (BW <2500 g), normal BW (NBW) (BW: 2500-4000 g) and high BW (HBW) (BW>4000 g). Results: This national survey was conducted among 23043 school students (participation rate: 92.6%). The mean age of participants (50.8% boys) was 12.54 ± 3.31 years. Results of multivariate logistic regression show that LBW increased odds of underweight (OR [odds ratio]: 1.61; 95% CI: 1.37, 1.89) and students with HBW had decreased odds of underweight (OR: 0.74; 95% CI: 0.58, 0.93) compared to students with NBW. Students with LBW compared to student with NBW had decreased odds of overweight (OR: 0.83; 95% CI: 0.69, 0.98) and general obesity (OR: 0.73; 95% CI: 0.56, 0.95). On the other hand, HBW increased odd of overweight (OR: 1.28; 95% CI: 1.09, 1.50), generalized obesity (OR: 1.59; 95% CI: 1.29, 1.96) and abdominal obesity (OR: 1.29; 95% CI: 1.11, 1.49) compared to NBW group. Conclusion: BW is a determinant of weight disorders and abdominal obesity in childhood and adolescence. This finding underscores the importance of prenatal care as well as close monitoring of the growth pattern of children born with low or high BW.